The Effect of Digital Marketing and Online Customer Reviews on Consumer Loyalty in the Shopee Marketplace Among 2022 Management Students at Tribhuwana Tunggadewi University, Malang - Rosalia Apri Linda; R.Y. Susanto; Imam Hidayat (International Research and Development for Human Beings (IRDH), 2026)
This study aims to analyze and explain the influence of Digital Marketing and Online Customer Reviews on Customer Loyalty among Shopee marketplace users. The research employed a quantitative explanatory approach. The population consisted of Management Department students from the 2022 batch at Universitas Tribhuwana Tunggadewi Malang. A sample of 73 respondents was selected using a purposive sampling technique. Data were collected through questionnaires that had been tested for validity and reliability. The data analysis technique utilized multiple linear regression analysis performed with SPSS software. Digital Marketing and Online Customer Reviews have a positive and significant influence on Consumer Loyalty on the Shopee platform. Partially, digital marketing has been proven to enhance consumer loyalty through ease of information access, content appeal, and effective digital interaction, as indicated by a significance value of 0.000 and a t-value of 9.118. Similarly, online customer reviews play an important role in building trust and creating long-term loyalty, with a significance value of 0.001 and a t-value of 3.400. Simultaneously, these two variables contribute 74.3% to consumer loyalty, while the remaining 25.7% is influenced by other factors such as price perception, service quality, and product quality. These findings emphasize that effective digital marketing strategies and credible management of customer reviews are key to maintaining Shopee user loyalty among students.